ANALISIS INFORMASI AKUNTANSI DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MENJUAL ATAU MEMPROSES LEBIH LANJUT KOPI BUBUK PADA TOKO SAMA JAYA MALANG - Gusnar Mustapa (STKIP PGRI TULUNGAGUNG, 2022)
This study aims to determine how the application of differential accounting information analysis to sell or process further that can be done by Toko Kopi Powder Sama Jaya in making decisions to increase company profits. The research method used in this research is to use a qualitative approach with the type of case study research. The data obtained in this study were sourced from original data obtained through interviews and documentation. Through analysis using differential accounting information, it can be seen the comparison between selling direct products and products that have been further processed. For the sale of ground coffee products, the company earns a profit of Rp 16,371,453.85 per day or Rp 40,928.32 for 1 (one) kilogram. Meanwhile, the sales of advanced products, namely 250 milliliters of milk coffee, the projected differential profit that will be obtained is Rp. 20,933,653.85 if all products are sold out on that day or Rp. 52,334.00 for every 1 (one) kilogram of ground coffee which is processed into 50 bottles. drink. This shows that differential accounting information can provide alternative decisions by calculating and analyzing differential costs and differential income so that differential profit projections are presented as a basis for decision making for management to increase company profits.